Identifying neonatal hyperglycemia thresholds in preterm infants based on retinopathy of prematurity outcomes: proof-of-concept study - Movsas, Tammy; Nadernejad, Claudia; Prentice, Jeannette; Dudick, Brooke; Pribyl, Amy; Sanfilippo, Lena; Geddie, Brooke E. (Frontiers in Pediatrics, 2025)
PurposeNeonatal hyperglycemia significantly increases risk for retinopathy of prematurity (ROP) in preterm infants, independent of other major ROP risk factors. However, glucose thresholds predictive of ROP remain undefined. This prospective study explored two glycemic metrics—mean blood glucose and glycated hemoglobin [specifically, glycated fetal hemoglobin for non-transfused infants and a neonatal-adapted hemoglobin A1C assay for transfused infants]—to identify thresholds associated with severe ROP.MethodsInfants born at gestational ages <30 weeks and hospitalized at DeVos Children's Hospital (September 2022–August 2024) were eligible. The final cohort included 98 infants. Blood glucose was monitored per clinical care, and glycated hemoglobin was measured on Day 30 using a research prototype assay. Eye exams were conducted per ROP protocol. Predictive thresholds for each biomarker were evaluated using AUC–ROC analysis.ResultsMost cases of severe ROP occurred in the transfused participants, who represent the earliest gestational ages and sickest infants. Both glycated hemoglobin (A1C) and 30-day mean blood glucose were significantly higher in infants with severe ROP compared to counterparts with mild or no ROP. Both biomarkers demonstrated concordant positive predictive values of 94%. Predictive cutoffs were identified as 5.66% for A1C (p = 0.003) and 93.8 mg/dl for 30-day mean glucose (p < 0.001).ConclusionsSevere ROP may represent a clinical outcome for defining neonatal glycemic thresholds. In this pilot study, preliminary cutoffs for two independent glycemic biomarkers are lower than current NICU intervention criteria; further investigation is needed to potentially refine glucose strategies for ROP mitigation.